2021
DOI: 10.1002/mame.202100004
|View full text |Cite
|
Sign up to set email alerts
|

Full Bio‐Based Soy Protein Isolate Film Enhanced by Chicken Feather Keratin

Abstract: Soy protein isolate (SPI) film is considered a promising biomaterial for the replacement of petroleum‐based food packaging plastics. However, current SPI films are still replying on petroleum‐based crosslink agents. In this paper, a green and effective approach is developed to prepare a full biomass‐based sustainable film with high strength and toughness by incorporating feather keratin (FK, extracted from the waste chicken feathers) into the SPI via the reaction of disulfide bonds. The broken disulfide bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…A wide plethora of biodegradable polymers, such as polysaccharides, proteins, and lipids, were proposed as suitable materials for thin-film preparation [6,12,13]. In this context, poly(butylene adipate-co-terephthalate) (PBAT) is an aliphatic/aromatic copolyester that is biodegradable and compostable and, due to its interesting properties, is considered among the most promising biopolymers for packaging film, agricultural film, and compost bag fabrication [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A wide plethora of biodegradable polymers, such as polysaccharides, proteins, and lipids, were proposed as suitable materials for thin-film preparation [6,12,13]. In this context, poly(butylene adipate-co-terephthalate) (PBAT) is an aliphatic/aromatic copolyester that is biodegradable and compostable and, due to its interesting properties, is considered among the most promising biopolymers for packaging film, agricultural film, and compost bag fabrication [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…1 was recorded as PM.1, and so on. Accordingly, in the TGA curves of MCM-41 and the phloridzin/MCM-41 assembly, slight weight loss was detected when the temperature was raised from 35 °C to about 100 °C, corresponding to the water loss [ 40 ]. At about 950 °C, the weight loss of the sample was minimal, indicating that most of the phloridzin had decomposed.…”
Section: Resultsmentioning
confidence: 99%
“…[33] The broad and strong absorption band at 3303 cm −1 was attributed to free/unbound -O-H and -N-H stretching vibrations. [34] After adding PAE and TA, the peaks shifted to lower wavenumbers (3280 to 3269, 3272, and 3258 cm −1 ) due to the formation of hydrogen bonds between SM, PAE, and TA in the adhesive system. In the SMT and SMPT adhesive sample, the vibration peak became considerably weaker around 1391 cm −1 (COO-bending) which revealed that weakened vibrational energy of the COO-bending was might be due to interactions with the catechol/pyrogallol and -OH.…”
Section: Design and Characterization Of The Smpt Adhesivementioning
confidence: 99%